«Proletarian revolutionary» autobiography – security deposit to the «early Soviet» generation of scientists (on the example of the scientific community of Odessa humanities) - Левченко, Валерій (V. N. Karazin Kharkiv National University Bulletin History of Ukraine. Ukrainian Studies: Historical and Philosophical Sciences, 2019)
The article proposes a model for studying the laws of formation, development, dissemination of scientific knowledge and paradigm changes among humanities scientists of the Odessa scientific community through the prism of identity of one generation. The interpretation of the term «generation» is formulated and a chronological periodization of generations of Odessa humanities scientists is proposed. The formulation of the names of the generations of the Odessa scientific community is differentiated in accordance with the ideological component of the dominant types of professional activity for each individual generation of Odessa scientists, which depended in each individually selected chronological period on the prevailing priorities of the formation of professional activity and the prosopographic palette of generation against the background of metamorphoses of available socio-political and sociocultural landscapes. Outlined the characteristic features of the «early Soviet» generation of Odessa scientists. The specifics of the relationship of Odessa humanities scientists with the current political regime, which had a multi-level structure. The main component influencing the activities of scientists was a complex permanent process of institutional, structural and cognitive changes in the public administration system. Against the background of socio-political changes of 1920–1941, the identities of individual Odessa scientists as representatives of the «early Soviet» generation were identified and represented. The gradual pulling of scientists into the yoke of official ideology and party-state control was noted, which led them to fear of the current government, disagreement with which led to a limitation of academic freedom, which manifested itself in total regulation and standardization of professional activity and various oppressions. As a result of which they were forced to indicate facts in their autobiographies that demonstrated their proletarian origin or their participation in revolutionary events on the side of the Bolsheviks.